2021 Cattlemen's Day Research Report (Kansas Agricultural Experiment Station Research Reports, 2021)
This report includes research on beef cattle management, reproduction, nutrition, and meat science conducted at Kansas State University. Specific topics include effects of prescribed burning and grazing in the Flint Hills, stocker steer gains, video sale prices and factors, vaccinations, carcass traits, limit-fed diet practices and effects, activity tracking technology capabilities, meat toughness and tenderness factors, and sensory evaluations of plant-based protein alternatives vs. ground beef.
Keywords: beef cattle management; reproduction; nutrition; meat science; prescribed burning; grazing